A Disturbing Hypothesis: Levinas as Political Theologian - Fonti, Diego (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
The question on the relationship of theology and politics is often reduced to circumstantial and emergent situations, thus hiding the structural aspects of this relationship. The philosophical tradition of political theology was able to formulate a theory of this relationship, which is influential even nowadays. The purpose of this essay is to research philosophically to what extent Levinas᾿ work, which is explicitly reluctant in front of theology and politics, may be placed within this tradition by structurally maintaining some of its essential aspects. Exception, decision and eschatology may be identified in Levinas, who resignifies them radically. This new meaning is powerful insofar it allows to keep the demands of political theology in a time where religious and axiological unity are not an option, and where democracy is in need of a foundation that may lead it towards the demands of radical justice and equality.